Decision Support System for Drafting of Sustainable Agriculture Production Policy for Odisha - Banashri Rath (International Journal of Supply Chain Management, 2013)
Agriculture production planning must aims at sustainability and progress at the same time. Production policy has farmers, government officials, political party, inputs for production, finance, market demand and pace of development as drivers for policy formulation. Selection of crops sequence in a geographical area is very difficult as it has sustainability parameter inbuilt in to policy. DSS can assist the policy planners to get different baskets of options for choosing the best SMART basket of option. The variation of rain- fall, climatic factors, and market trend of different crops have been considered to frame the basket of crops options to be grown in a hilly district of Odisha, India. The DSS formulation has inbuilt mechanisms for blending of the qualitative and quantitative parameters used in crop sequence planning in the agricultural policy. With reduction in rainfall, there is a chance that the paddy crop growing may not be feasible. Some low water requiring crops are used to determine the other basket of option. Under present context, KBK region of Odisha, India with less rain fall can have the best alternate crop as per the residual moisture has been found to be pulses crop for hilly area of the state. Similarly the area with higher rainfall can have paddy paddy cropping pattern as per present practice. However there is scope for cash crops like maize, groundnut in the crop sequence. Keywords DSS, KBK, Cropping Sequence, Cash Crops, SMART,